Study of the State of Industrial P2O5‐Containing Slags Relevant to Steelmaking Processes Based on a New Thermodynamic Database Developed for CaO–FeOx–P2O5–SiO2–MnO–MgO–Al2O3 Slags − Part I: Ternary and Lower Order Systems. Issue 8 (5th June 2019) - Khadhraoui, Sabrine; Hack, Klaus; Jantzen, Tatjana; Odenthal, Hans‐Jürgen
Abstract : During oxygen refining of steel, the slag undergoes large variations in terms of its composition, temperature, and oxygen partial pressure. This paper presents a study of the state of CaO–FeO x –P2 O5 and CaO–FeO x –SiO2 based slags under various process conditions by means of thermodynamic calculations using a newly developed thermodynamic database. The database is developed in the scope of the European project BOF DePhos (RFSR‐CT‐2014‐00005) for the purpose of investigating different thermodynamic aspects of phosphorous containing steelmaking slags in the composition, temperature, and oxygen partial pressure ranges relevant for the industrial process. The non‐ideal associate solution model is used for the description of the Gibbs energy of the liquid phase and the compound energy formalism (CEF) for the description of the Gibbs energy of the solid solution phases. By means of coupling the thermodynamic database to the Software FactSage™, the state of the quasi‐ternary oxide systems CaO–FeO x –P2 O5 and CaO–FeO x –SiO2 systems relevant to low and high phosphorus refining processes, respectively, is investigated. The results of the calculations are compared with reported experimental data in the literature and indicate that the incorporation of the effect of oxygen partial pressure p(O2 ), and thus that of the oxidation state of FeO x, is crucial for a proper modeling and assessment of the state of industrial BOF slags. With an increase in p(O2 ), a considerable increase in lime saturation for both quasi‐ternary systems is observed and a shrinkage in the silicate saturation regions for the CaO–FeO x –SiO2 system occurs. The consequences of the findings for the industrial process are discussed. Mathematical descriptions of the dependency of lime saturation on temperature and oxidation state of FeO x in the ternary systems are provided. Abstract : BOF slags undergo large variations in terms of temperature and oxidation state during the oxygen blow. By application of a computational thermodynamics approach, the effect of varying process conditions is investigated. The phase diagrams relevant to high and low Phosphorous refining processes are presented and new insights into the state of industrial slags are gained. The figure shows an overview of the effect of process conditions (oxidizing/reducing) on the CaO–FeO x –P2 O5 system relevant for high phosphorous slags: The solid lines represent the high oxidation state whereas the dashed lines represent the low oxidation state and comparison with experimental measurements (data points) in the literature.